Application of the Direct Oral Anticoagulants to Thromboprophylaxis of Mechanical Heart Valves - Jaffer, Iqbal H (My University, 2017)
Patients with valvular pathology who require heart valve replacement surgery are faced with the option between a bioprosthetic heart valve (BHV) or a mechanical heart valve (MHV). BHVs have a limited lifespan and are prone to structural degeneration. In contrast, MHVs are free from structural deterioration, but necessitate lifelong anticoagulation due to a more robust activation of coagulation. This is usually achieved in the outpatient setting with the use of vitamin K antagonists (VKAs), such as warfarin. Due to the cumbersomeness of managing warfarin with regular monitoring and its numerous food- and drug-drug interactions, other oral anticoagulants were sought. Within the last decade, the advent of the direct oral anticoagulants (DOACs) has largely supplanted warfarin and other VKAs for numerous indications, including stroke prevention in atrial fibrillation and prevention and treatment of venous thromboembolism. When evaluated in a clinical trial in patients with MHVs however, use of the thrombin-directed DOAC, dabigatran, led to an increase in both bleeding and clotting; prompting a halt to the study and a black box warning against the use of dabigatran and other DOACs in patients with MHVs. The cause of this failure at the time was not understood and prompted the investigations detailed in this thesis. The work described within this thesis sought primarily to understand why dabigatran failed to adequately provide thrombo-protection for patients with MHVs. Firstly, the mechanism of thrombin generation on MHVs was identified as being initiated and propagated through the contact and intrinsic pathways, respectively. Within this same work, a mechanism for the failure of dabigatran and the efficacy of warfarin was presented. It was shown that dabigatran concentrations of greater than 250ng/mL were required to suppress thrombin generation, whereas the same effect could be achieved with warfarin at an INR of 1.5 or greater. Secondly, the effect of the other DOACs, rivaroxaban and apixaban, on MHV-induced thrombin generation was assessed, and we showed that individually, these two DOACs were unable to suppress thrombin generation within clinically-relevant dosing regimens. We also evaluated a combination of dabigatran and rivaroxaban to determine whether the combination would be superior to either agent alone at suppressing MHV-induced thrombin generation. Lastly, the capacity of two assays – the ecarin chromogenic assay and the dilute thrombin time – to detect both on treatment and low levels of dabigatran is presented as a tool for clinicians to determine whether patients taking dabigatran can safely undergo procedures or whether they necessitate rapid reversal in emergent situations.
Keywords: Anticoagulation; Heart Valves; Coagulation